Puzzles in bonding and spectroscopy: the case of dicarbon. (1st March 2016) - Macrae, Roderick
The unstable molecule C2 has been of interest since its identification as the source of the "Swan band" features observable in the spectra of flames, carbon arcs, white dwarf stars, and comets, and it continues to serve as a focal point for experimental and theoretical discovery. Recent spectroscopic work has identified a quintet state of the molecule for the first time, while new insights into the bond order of C2 in its ground state have been provided by sophisticated computational methods based on valence bond theory. This article gives a review of spectroscopic and computational work on C2 including both historical background and the most recent discoveries.